The Effect Of Know - Want To Know – Learn Method In Reading Skills Of Grade X At Sma Swasta Al Washliyah 2 Serbelawan - Rohdearni Wati Sipayung; Semaria Eva Elita Girsang; Nanda Nadila Damanik (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2023)
The aim of this research is to find out the significant effect of using KWL Method in reading skills of grade X of SMA Swasta Al Washliyah 2 Serbelawan. This research used quantitative method approach. Population of this research was grade X with one class which consists of 23 students. The technique of collecting data was pre-test and post-test. The technique analysis data by using formula. The result of this research was obtained tcount=10,86 > ttable= 1,717 at the significance level ɑ=0.05 and degrees of freedom (df)= 22, Ho is rejected and Ha is accepted and implies that the students taught by using KWL Method achieve a better score. It means that there is significant effect of using KWL Method in Reading Skills of Grade X at SMA Swasta Al Washliyah 2 Serbelawan. Because the using KWL Method as a method for learning English to reading ability. KWL Method a variety of features, including a dictation function, which makes it easier for students to learn and understand English as reading skills. The students should from a habit of reading by using KWL method to improve their reading skills